RAB7 GTPases as coordinators of plant endomembrane traffic - Rodriguez-Furlan, Cecilia; Borna, Rita; Betz, Oliver (Frontiers in Plant Science, 2023)
The ras gene from rat brain (RAB) family of small GTPases is highly conserved among eukaryotes and regulates endomembrane trafficking pathways. RAB7, in particular, has been linked to various processes involved in regulating endocytic and autophagic pathways. Plants have several copies of RAB7 proteins that reflect the intricacy of their endomembrane transport systems. RAB7 activity regulates different pathways of endomembrane trafficking in plants: (1) endocytic traffic to the vacuole; (2) biosynthetic traffic to the vacuole; and (3) recycling from the late endosome to the secretory pathway. RAB7 governs the course of autophagic trafficking when autophagy is activated due to developmental processes or stress responses (4). RAB7s carry out these functions by interacting with various effector proteins. Current research reveals many unexplored RAB7 functions in connection with stress responses. Thus, this review describes a comprehensive summary of current knowledge of plant RAB7's functions, discusses unresolved challenges, and recommends prospective future research directions.